Kinetic-hybrid Simulations of Counterpropagating Ion Cyclotron Waves and Proton Scattering in the Near-Sun Solar Wind - Yifan Wu; Chen Shi; Xin Tao; Jinsong Zhao (The Astrophysical Journal)
Ion cyclotron waves (ICWs) are prevalent in the near-Sun solar wind and play a significant role in the nonadiabatic heating of plasma. Recent observations from the Parker Solar Probe have revealed the simultaneous presence of antisunward and sunward ICWs in the vicinity of the Alfvén surface. However, single-satellite observations cannot effectively trace the generation and evolution of these observed waves. To address this limitation, we employ kinetic-hybrid simulations to replicate the generation and evolution of counterpropagating ICWs under typical plasma conditions in the near-Sun solar wind. Following the linear growth phase, the simulated waves exhibit amplitude and polarization characteristics that closely match the observations. Additionally, our simulation illustrates proton scattering induced by the counterpropagating waves. These results underscore the significance of locally generated ICWs in influencing solar wind ion dynamics.